MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DI STAIN PAMEKASAN - M. Muchlis Solichin (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2011)
Mediums management and pre-mediums represent an absolute done in an higher education institute, because Mediums and premediums in education management represent the absolut condition in the effort to reach the target which is expected. Thereby, Every the education organizer have to pay attention and conscripting the mind and energy to carry out education management that is professional and fulfill Standard National Education ( SNP). This Research copes to comprehend the mediums and pre-mediums management of education in STAIN Pamekasan, because during this time of mediums and basic mediums management are not yet showing its idealitas. This research is focussed at; a) How mediums and pre-mediums menegement in STAIN Pamekasan ?,and b) what Factors influencing mediums and pre-mediums management in STAIN Pamekasan ?. This research uses the qualitative type by using observation, interview, and documentation method. Based the rearch done, to be expressed that the first of STAIN Pamekasan conduct mediums and pre-mediums manegement still have the centralization character of top down), either in the case of planning, organizational, observation, and assessment of mediums and pre-mediums management owned, second in some cases of STAIN Pamekasan do not yet manage the mediums and pre-mediums management because they are caused by factor is its lack of management professionalism, either when doing the planning, organizational, treatment and observation or evaluation. Based the matter above, hence, suggested that STAIN Pamekasan carry out the mediums and pre-mediums management of education professionally.